Pengaruh Dana Pihak Ketiga dan Kredit Bermasalah terhadap Penyaluran Kredit pada Lembaga Perkreditan Desa (LPD) Sekecamatan Kediri Kabupaten Tabanan - Ni Wayan Ayu Utari; Kompiang Bagiada; I Gst Ayu Athina Wulandari (Warmadewa Economic Development Journal (WEDJ), 2020)
The research entitled Effect of Third Party Funds and Problematic Loans on Credit Distribution at Village Credit Institutions (LPD) in Kediri District, Tabanan Regency. The formulation of the problem is: How to Influence Third Party Funds and Troubled Loans simultaneously and partially on Credit Distribution LPD in the Kediri District. The Research Objective is to find out how the influence of Third Party Funds and Problematic Loans Against Credit Distribution In the LPD of Kediri District. Data analysis is done by dummy variables and hypothesis testing with multiple linear regression analysis methods. The results showed that partially Third Party Funds had a positive and significant effect on Credit Distribution while Problematic Loans had a negative and not significant effect on Credit Distribution. Simultaneously Third Party Funds and Troubled Loans significantly influence Credit Distribution at the Kediri District LPD.